GAGASAN PENGISIAN JABATAN PENJABAT KEPALA DAERAH DIKAITKAN DENGAN ASAS AKUNTABILITAS DI INDONESIA - Hafifatul Nesya; Dessy Artina; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Filling in the position of acting regional head (Pj) which is carried out using anappointment mechanism by the president and the minister of home affairs is considered nottransparent, accountable and participatory and ignores democratic principles. The centralgovernment has a central role in appointing acting regional heads without involving theaspirations of the regions, and there is no clear and firm legal regulation regarding fillingthe positions of acting regional heads which is increasingly causing polemics in society.This study uses normative legal research methods by collecting literature andfocusing on legal principles, namely the general principle of good governance (AUPB) infilling the positions of acting regional heads in accordance with the principle ofaccountability in Indonesia.The results of the study show that, first, the dynamics of filling the vacant positions ofregional heads in Indonesia from the old order era to the reform era were carried outcentrally with power in the hands of the central government. This is reflected in severalstatutory provisions in force in Indonesia which are the government's reference in filling thevacant regional head positions. Second, filling the position of acting regional head is seen asnot being transparent, participatory and accountable and setting aside democratic values byignoring the aspirations of the region and the people. The central government is nottransparent and accountable in appointing acting regional heads so that the mechanism forappointing acting regional heads creates polemics in society. Third, the legal regulationsregarding acting regional heads should be issued immediately so that the filling of regionalhead positions has a clear and firm measurable mechanism and continues to be transparent,accountable and participatory as mandated in the Constitutional Court decision with caseNumber 67/PUU-XIX/2021 and Article 86 paragraph (6) of Law Number 23 of 2014concerning Regional Government, with contents including: a) involving the DPRD in theprocess of proposing candidates for acting regional heads b) participation of the regionalpeople in providing suggestions and input regarding the performance of the acting (Pj)regional head, c) the existence of mechanisms and prerequisites that are clearly measurableand filling the positions of acting regional heads so that they remain in accordance with thegeneral principles of good governance that are transparent, participatory and accountable.Keywords: Idea, Filling in the Position of Acting Regional Head, Accountability